The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1177/0091270007311569
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of SLCO1B1 Polymorphism on the Pharmacokinetics and Pharmacodynamics of Repaglinide and Nateglinide

Abstract: Thirty-two healthy volunteers with different SLCO1B1 genotypes ingested a 0.5-mg dose of repaglinide and 60-mg dose of nateglinide with a washout period of 1 week. Participants with SLCO1B1 c.521CC genotype (n = 4) had a 59% (P = 0.001) or 72% (P < 0.001) greater mean area under the plasma repaglinide concentration-time curve (AUC(0-infinity)) than participants with c.521TC (n = 12) or c.521TT (n = 16) genotypes. The AUC(0-infinity) of repaglinide metabolites M2 and M4 were 112% (P = 0.004) and 81% (P = 0.002)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(17 citation statements)
references
References 47 publications
(138 reference statements)
0
16
0
1
Order By: Relevance
“…The notion of rosiglitazone as a putative OATP1B1 substrate was further strengthened by existing drug-drug interaction data showing that rosiglitazone concentrations were increased following administration of gemfibrozil, which has both OATP1B1- and CYP2C8-inhibitory actions [34]. Polymorphisms in SLCO1B1 , particularly 521 T > C, have been shown significantly to alter the pharmacokinetics of substrates such as pravastatin and repaglinide [28-30]. Therefore, it can be hypothesised that if rosiglitazone is indeed an OATP1B1 substrate, plasma drug exposure would be higher in subjects carrying a variant SLCO1B1 521C allele, as a result of diminished substrate uptake in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The notion of rosiglitazone as a putative OATP1B1 substrate was further strengthened by existing drug-drug interaction data showing that rosiglitazone concentrations were increased following administration of gemfibrozil, which has both OATP1B1- and CYP2C8-inhibitory actions [34]. Polymorphisms in SLCO1B1 , particularly 521 T > C, have been shown significantly to alter the pharmacokinetics of substrates such as pravastatin and repaglinide [28-30]. Therefore, it can be hypothesised that if rosiglitazone is indeed an OATP1B1 substrate, plasma drug exposure would be higher in subjects carrying a variant SLCO1B1 521C allele, as a result of diminished substrate uptake in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis in East Asians confirmed that KCNQ1 rs2237892 was the polymorphism most strongly associated with T2DM susceptibility9. In addition, KCNQ1 also influences the efficacy of repaglinide; however, the underlying mechanisms remain unclear101112. A clinical study demonstrated that diabetic patients with the KCNQ1 rs2237892 T allele were more likely to have a positive response to repaglinide, while patients with the KCNQ1 rs2237892 C allele exhibited larger increases in HOMA-IR13.…”
mentioning
confidence: 98%
“…Pharmacokinetics of both of these glinide drugs is also influenced by variant 521T>C in SLCO1B1 , the gene encoding organic anionic transporter B1 (OATPB1) [15]. …”
Section: Pharmacogenetics Of Insulin Secretagoguesmentioning
confidence: 99%